Kanalisering och restaurering av vattendrag och dess påverkan på mossamhällen i strandzonen - Knudsen, Carola (Karlstads universitet, Fakulteten för hälsa, natur- och teknikvetenskap (from 2013), 2019)
In the 1850s when the timber floating began in Sweden many streams were channelized, which meant that the streams were straightened out, side channels were closed, and stones, trees and boulders were moved out to the banks of the streams. These measures altered the morphology of the streams, causing impediments to water moving in from the stream to the riparian zone, and reduced flooding frequency. When the era of timber floating was over humans began to restore the channelized streams to restore the damaged systems, mainly to improve fish habitats. Channelization and restoration involve major disruptions to the stream ecosystem, and the purpose of this study was to investigate how the bryophyte communities in the riparian zone differed in diversity, species richness and areal coverage, depending on the form of disturbance they were exposed to and the time passed since the disturbance occurred. This study was conducted along tributaries to the Vindel River in northern Sweden. There were three types of tributaries: partly channelized streams, best-practice restored streams and demonstration restored streams. At all tributaries included in the study, bryophyte samples were collected at two heights from the water surface, 0 and 40 cm. These samples were then identified to family or species level and their areal coverage was estimated. The results show that the demonstration restored streams had the lowest species richness and, there were no significant differences in diversity and species richness between the channelized streams and the best-practice restored streams. Regarding areal coverage, there was no significant difference between the stream types. The results also show that the time plays an important role for recovery of the bryophyte communities since diversity and species richness increased with the time since the disturbance occurred. Under 1850-talet då flottning av timmer påbörjades i Sverige startade kanaliseringen av många vattendrag, vilket innebar att vattendragen rätades ut, sidokanaler ...